The concept and notion of “Security” – a comparative and functional approach - Aishah Bidin, (Fakulti Undang - Undang, 2001)

(untitled)
In recent times there has been a substantial increase in the number of issues requiring analysis in the process of determining which transactions should come within the definition of a ‘security’. This is especially true since there have been many new financial instruments and techniques introduced to the international capital markets. The concept of security in this article is focused on its traditional definition. However, the term “security” is susceptible to more than one definition. Indeed, as the term is now commonly used to describe virtually any form of financial instrument used in connection with a loan, a discussion of corporate securities is also included in this paper. Regardless of how the term is used, the issuance of security confers certain “rights” and “interests” to the creditor. Thus, this paper will evaluate not only the genesis, but also the general notion of security, how it has been applied in different factual situations and the different implications that can be drawn from these varying applications namely in the United Kingdom and Malaysia